Analysis of Student Needs for the Development of a Web-Based Cyber Counseling System to Support MBKM in Higher Education - Hidayat, Rahmat (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to determine student needs for the development of a web-based cyber counseling system to support the implementation of the MBKM curriculum in universities. The data analysis technique is done by analyzing qualitative and quantitative data analysis and concluded using qualitative analysis. This research is part of R & D research with the 4D development method which is limited to the define and design stage. The stages used in this research are the needs analysis and design stages, the instruments used in this research are observation sheets, interview sheets, and questionnaires for cyber counseling needs in universities. Data collection techniques used observation data, interviews, and questionnaires using Google Forms. The sample data in this study were 111 Guidance Counseling students at Bengkulu University from semesters 1, 3, 5, and 7. The results showed that students strongly agreed that the development of a Web-based Cyber Counseling system was needed to support MBKM in universities.